Uso problemático de internet e adição ao facebook são o mesmo construto latente? - Silva, Hugo Rafael de Souza e [UNIFESP] (2016)
Introduction: Problematic Internet Use (UPI) and Facebook Addiction (AF) are issues that have become common in psychiatric, researchers and families discussions. Some countries already regard them as public health problems, due to prevalence, magnitude, transcendence and impact on the daily lives of affected people. Technological additions have no widely accepted diagnostic criteria that it difficult to identify and overall assessment of this group of disorders. Facebook addiction has been crafted as a UPI distinct clinical adversity even being noticeable that has common features. However, social networks are content/websites with specific purpose on the internet and could not be seen separately as part of the UPI spectrum/continuum. Objective: To determine whether the Facebook addiction and the Problematic Internet Use (UPI) are the same theoretical latent construct. Methodology: This is a cross-sectional study of health university students aged ? 18 years. 382 students enrolled was interviewed during the study period in health graduate courses at the University of Pernambuco (UPE). The study was divided into two stages. The first step was the semantic equivalence and verbal comprehension analysis of two psychometric instruments: Online Cognition Scale (OCS) and Bergen Facebook Addiction Scale (BFAS). For this first step were carried out the translation; back translation; technical review and evaluation of the semantic equivalence by qualified professionals; instrument evaluation as verbal comprehension by a sample of professionals (n = 10) and students (n = 37) of the instruments. After completion of this step, the second step was started with psychometrics qualities study of the instruments, through the reliabiblity analysis and construct validity of three instruments: Portuguese version of the OCS and BFAS and a socio demographic questionnaire. Reliability was verified by internal consistency analysis and instrument stability in the time through Cronbach's alpha and intraclass correlation coefficient (ICC) respectively. Construct validity analysis was verified by confirmatory factor analysis (CFA) that estimates the factorial and convergent validity indicators and model adjustment quality. For the analysis of adjustment quality were verified by the following indicators: ?2/df p<0,05; GFI > 0,90, CFI > 0,90, RMSEA ? 0,05. Factorial validity is achieved when the standardized factor load (?2) is greater than 0.25. Convergent validity is checked when the average extracted variance (AEV) ? 0.5, construct reliability (CR) ? 0.7 and when the manifest variables present factor loads (?) ? 0.5. Discriminant validity between the constructs Facebook addition and UPI was verified by correlation analysis. It is considered that two constructs differ when the correlation coefficient ? 0.7. Another strategy of discriminant validity analysis is recommended by Fornell Larcker (1981) to suggest that to be discriminant validity between two constructs the average extracted variance (AEV) of each construct should be greater than the square of the correlation between them. Results: Both instruments showed an excellent level of verbal comprehension by the target population. BFAS presented Cronbach's alpha of 0.92 and CCI of 0.8 and OCS showed Cronbach's alpha of 0.91 and ICC of 0.91. Final factor structure of BFAS appropriate adjustment: ?2/df = 1,13 (p=0,341), GFI=0,99, CFI=0,99, RMSEA=0,01 and MECVI= 0,103, reaching convergent validity indicators satisfactory (AEV = 0.49, CR = 0.84). The correlation between the Portuguese version of the BFAS and OCS was ? = 0.707. The Portuguese version of OCS revealed the following satisfactory quality indicators ?2/df = 1,759 (p=0,171), GFI=0,99, CFI=0,99, RMSEA=0,04 and ECVI= 0,05. Convergent validity indicators were adequate CR = 0.85 and AEV = 0.59. Validity analysis of the correlation between the constructs Facebook Addiction and UPI revealed a correlation coefficient ? = 0.707 (p <0.001). The average variance of each individual construct (UPI and Facebook Addiction) were AEVFA= 0.51 and AEVPIU = 0.58, both below the square of the correlation between both constructs ? = 0.73 (p <0.001 ). Conclusion: The methodological rigor employed in the steps of semantic equivalence ensure the Portuguese versions of the instruments achieved the transfer of referential and general meanings, besides to show good rates of verbal understanding. Both instruments are reliable with good internal consistency indicators and stability over time. Producted versions in this study exhibited sufficient evidence of construct validity. Finally, there was no sufficient evidence that the constructs UPI and AF are distinct and independent of one another.